Effect of Price and Promotion on Car Purchase Decisions at PT Encar Daihatsu Lubuklinggau - Supriyanto Supriyanto; Ronal Aprianto Ronal; Melvin Melisa (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
The purpose of this study was to determine the effect of price and promotion on car purchasing decisions at PT Encar Daihatsu, Lubuklinggau City. The population in this study was 138 and the sample was 58 respondents. The data analysis method used is the regression test, correlation coefficient test, t test, determination coefficient test, and F test. Price results (X1) on Purchase Decisions (Y) have a significant effect with tcount of 5.074> t-table value of 1.673 significant 0.000 < 0.05. Promotion Results (X2) on Purchase Decisions (Y) have a significant effect with the tcount of 4.499> the ttable value of 1.673 significant 0.000 <0.05. Price (X1) and Promotion (X2) on Purchase Decision (Y) have a significant effect with the value of Fcount (27.461)> Ftable (3.18) significant 0.000 <0.05. The conclusion is that Price and Promotion have partial or simultaneous effect on Car Purchase Decisions at PT Encar Daihatsu, Lubuklinggau City.